(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the views of Eastern thinkers on learning activity motivation and personal development. The study examines the psychological and pedagogical ideas of Abu Bakr ar-Razi, Abu Nasr al-Farabi, and Abu Rayhan al-Biruni concerning learning motivation, aspiration for knowledge, interest, moral purity, and teacher–student relationships. These ideas are interpreted from the perspective of modern educational psychology, emphasizing the importance of intrinsic motivation in learning activities. The article highlights the relevance of Eastern pedagogical heritage in the contemporary education system.